The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/ssr-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian Junior Football Players – Player’S Perception Of Stress According To Playing Time

Abstract: T his study's purpose was to investigate how junior football players representing a professional club experienced stressors according to there given playing time. Participants (N43) represented 3 football clubs (mean 17.4 yrs). The results showed that the players playing all matches reported a lower level of stress related to performance and future stress compared to the players playing few matches. Furthermore, evaluation and performance stress was reported higher among player given few matches compared to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Th e results showed that 2016 players reported signifi cantly less evaluation stress and development stress and significantly more academic stress compared to 2013. As a group, players have thus had a positive development in view of a reduced evaluation stress, which in previous studies has proved challenging for junior players with little playtime (Saether, & Aspvik, 2016;Saether et al, 2017). Th is indicates that players to a lesser extent feel their existence in the football academy as a threat but are able to handle the stressors.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Th e results showed that 2016 players reported signifi cantly less evaluation stress and development stress and significantly more academic stress compared to 2013. As a group, players have thus had a positive development in view of a reduced evaluation stress, which in previous studies has proved challenging for junior players with little playtime (Saether, & Aspvik, 2016;Saether et al, 2017). Th is indicates that players to a lesser extent feel their existence in the football academy as a threat but are able to handle the stressors.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study of junior players in three Norwegian top clubs showed that players who had the least play time reported signifi cantly more stress performance and evaluation stress to the players who had more play than them (Saether, & Aspvik, 2016). Another study of academics from two Norwegian top clubs showed that players who considered themselves as less skilled compared to their teammates reported signifi cantly more performance stress (Saether, Aspvik, & Høigaard, 2017).…”
Section: Th Eoretical Frameworkmentioning
confidence: 96%
See 3 more Smart Citations